Genevan sex crimes database, c.1440-c.1790 - Naphy, William G. (UK Data Service, 2002)
The study examined in detail over 300 criminal trials surviving in Geneva relating to sexual deviance (homosexuality, male rape/sexual assault, paedophilia, lesbianism, bestiality, adolescent sexual experimentation, female rape/sexual assault, adultery and fornication). These trials, in which verbatim testimony and numerous depositions by witnesses survive, give an ideal place to test pre-Freudian ideas of sexual development, sexual categories and sexual self-awareness.